Uso de sensores digitales de movimiento para menguar el desperdicio de agua potable en urinarios y lavatorios del colegio mons. Atanasio Jauregui Goiri de la ciudad de Yurimaguas - López Del Águila, Adrián (2014)
This project proposes to reduce water waste in school Goiri Jauregui Bishop Athanasius of Yurimaguas, using sensors in toilets, urinals, sinks the school and thus make efficient use of water resources. Since it has been shown that in public schools the toilets are the main point of waste, because the users themselves misuse services and the limited staff of the institution for maintenance. The research results obtained using the simulation show that there is a significant saving to the use of this technology equivalent to 52% of consumption. Whereupon the school may decide to purchase equipment allowing him to be an efficient institution in the use of water resources